Dietary supplementation with β-mannanase and probiotics as a strategy to improve laying hen performance and egg quality - Carvalho, Camila Lopes; Andretta, Ines; Galli, Gabriela Miotto; Bastos Stefanello, Thais; Camargo, Nathalia de Oliveira Telesca; Mendes, Ricardo Evandro; Pelisser, Giovanna; Balamuralikrishnan, Balasubramanian; Melchior, Raquel; Kipper, Marcos (Frontiers in Veterinary Science, 2023)
The objective of this study was to assess the impact of β-mannanase and probiotic on the performance, serum biochemistry, gut morphometric traits, and fresh egg quality of laying hens. A total of 120 cages, housing light-weight laying hens (36 weeks old), were randomly assigned to four different treatments. These treatments included a control group fed non-supplemented diets; diets supplemented with 300 g/ton of beta-mannanase; diets supplemented with 50 g/ton of probiotic; or diets containing both 300 g/ton of β-mannanase and 50 g/ton of probiotics. The trial spanned a duration of 26 weeks and was divided into three productive phases, each lasting 28 days. The inclusion of β-mannanase resulted in a significant improvement in the laying rate by 11% (p < 0.05) compared to the control treatment. Similarly, the addition of probiotics also enhanced the laying rate by 7% (p < 0.05), as well as the supplementation with combined additives (11.5%). Combined additives showed an increase in egg masses, and additive association improved by 13.9% (p < 0.001) in contrast to the control treatment. Overall, β-mannanase and combined additives used during the supplementation period resulted in improvements in the weight of fresh eggs. These benefits were observed after a period of 14 weeks without supplementation (p < 0.05). Furthermore, significant differences were observed in the serum biochemistry and egg masses of birds that were fed diets containing both additives (β-mannanase + probiotics) compared to the control group. Parameters such as uric acid, total cholesterol, and triglycerides displayed notable variations. The villi height: crypt depth showed differences with combined additives (β-mannanase + probiotics). The β-mannanase improved specific gravity, yolk height, length, and pH, and yolk color traits compared to the control treatment. The use of probiotics helped to improve yolk height, pH, and color score. Besides, combined additives (β-mannanase + probiotics) improve yolk height, length, weight, pH, and better traits in yolk color. Hence, incorporating β-mannanase and probiotics into laying hen diets proves to be a highly effective strategy for enhancing laying rate and overall health status, while simultaneously elevating certain quality attributes of fresh eggs.